The likeness - French, Tana. (New York : Viking, 2008)
Six months after the events of In the Woods, Detective Cassie Maddox is still trying to recover. She's transferred out of the murder squad and started a relationship with Detective Sam O'Neill, but she's too badly shaken to make a commitment to him or to her career. Then Sam calls her to the scene of his new case: a young woman found stabbed to death in a small town outside Dublin. The dead girl's ID says her name is Lexie Madison- -the identity Cassie used years ago as an undercover detective--and she looks exactly like Cassie.--From publisher description.
Sequel to "In the Woods."
Keywords: Women detectives -- Ireland -- Fiction; Murder -- Investigation -- Fiction; Suspense fiction; Mystery fiction